Allamah Shibli’s methods of authenticating Islamic historical facts - khan, Israr Ahmad (Bangladesh Institute of Islamic Though, 2015)
The Sirah (biography of the Prophet Muhammad) literature in general merely contains narration of historical events related directly or indirectly to the last Prophet (SAW). Allama Shibli Nu„mani‟s work entitled Sirat al-Nabi is an exception to this general trend. This article attempts to highlight AllamahShibli‟s methodology of Sirah writing in general, and analyze selected historical events as treated by him in his Sirat al-Nabi in particular in a bid to reconfirm the aptness of his investigation of Sirah-related events. The article has selected seven historical incidents and showed that Shibli Nu„mani has analysed the controversial stories in the light of three elements: the Qur‟an, authentic Hadith and the chain of narrators (sanad). Through this process, he identified what was fabricated and baselessly reported.